Assessment of heritability and genetic advance in soybean [(Glycine max (L.) Merrill)]: Assessment of heritability and genetic advance in soybean [(Glycine max (L.) Merrill)] - P MANJUNATH; T H RENUKA DEVI; M SURYA PRAKASH REDDY (Journal of Oilseeds Research, 2020)
Selection is effective only when the observed variability in the population is heritable in nature. Heritability estimates give a measure of transmission of characters from one generation to the other, as consistency in the performance of the selection depends on the heritable portion of the variability. Thirty advanced lines of soybean were evaluated in a randomized block design with three replications to estimate heritability and genetic advance for 11 agromorphological characters under rainfed conditions during kharif 2018. High heritability accompanied with high genetic advance expressed as percent of mean was recorded in seed yield/plant, harvest index, biological yield/plant, 100 seed weight, days to 50% flowering, days to maturity, plant height and oil content, which indicates the preponderance of additive gene effects and therefore these characters possess high selective value. Thus, selection for these characters can be done for their improvement.